Penguatan Perspektif Islam Dalam Pendekatan "STEAM" Bagi Anak Usia Dini : Studi Literatur Sistematis Tahun 2018-2026: Strengthening Islamic Perspectives in the "STEAM" Approach for Early Childhood: A Systematic Literature Review 2018-2026 - Mohamad Fauzil Adhim Asnawi; Diajeng Aulia (Qudwah: Journal of Islamic Education, 2026)
This study aims to examine how Islamic values ​​are integrated into STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning in early childhood education through a systematic literature review approach to scientific publications from 2018–2026. The review process was conducted by searching for articles indexed in the Scopus, Web of Science, and SINTA databases using the PRISMA framework to ensure transparent and systematic literature selection. The analysis results indicate that the integration of STEAM with an Islamic perspective plays a positive role in improving critical thinking skills, creativity, and strengthening the spiritual dimension of early childhood learners. The implementation of Islamic values ​​is reflected in three main domains: strengthening aspects of faith through scientific exploration that connects natural phenomena with the greatness of God, building morals through project-based collaborative activities, and developing spirituality through meaningful scientific reflection. These findings indicate that the STEAM approach integrated with Islamic values ​​has great potential as a holistic, contextual learning model oriented towards the formation of both scientific and religious character. Therefore, this study recommends the development of an adaptive curriculum, improving educator competency, and compiling STEAM-Islam-based teaching materials to support optimal implementation in early childhood education institutions.